Leader political skill and casino dealer morale: the mediating role of follower perceptions of leader-member exchange - Kim, Taegoo Terry; Karatepe, Osman M.; Lee, Gyehee; Lee, Choong-Ki (Springer Heidelberg, 2017)
Our study investigated the follower perceptions of leader-member exchange (FPLMX) as a mediator between leader political skill (LPS) and follower morale and tested these relationships using data obtained from casino dealers in Korea. Social astuteness, interpersonal influence, networking ability, and apparent sincerity are the indicators of LPS, while follower morale is composed of job satisfaction and affective organizational commitment. The results from structural equation modeling suggest that the research model we have proposed is viable. Broadly speaking, FPLMX is a partial mediator between LPS and follower morale.
Keywords: Casino industry; Employee morale; Leader political skill; Leader-member exchange; Leadership behavior